2023
DOI: 10.1242/dev.200623
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional control of developmental processes

Abstract: Nutritional and metabolic cues are integral to animal development. Organisms use them both as sustenance and environmental indicators, fueling, informing and influencing developmental decisions. Classical examples, such as the Warburg effect, clearly illustrate how genetic programs control metabolic changes. However, the way that nutrition and metabolism can also modulate or drive genetic programs to instruct developmental trajectories is much more elusive, owing to several difficulties including uncoupling pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Although it has been shown that for cultivating embryoids beyond the gastrulation stage in vitro, the precise and timely delivery of oxygen, glucose, and the appropriate culture media in specialized incubators is essential [20], there is no evidence that these factors have any direct instructive function for embryonic pattern (basic body plan) development. They should be seen as nutritional needs in a more general sense [37][38][39]. In earlier years, it had indeed been proposed by some researchers that axis development (the embryonic-abembryonic axis, i.e., the precursor for the dorsoventral axis; the anterior-posterior axis), and the laying down of the basic body plan at gastrulation, might be determined by uterine factors (secreted factors or cellular interactions at implantation).…”
Section: A Recent Discussion About Ethical Guidelines and The Term "E...mentioning
confidence: 99%
“…Although it has been shown that for cultivating embryoids beyond the gastrulation stage in vitro, the precise and timely delivery of oxygen, glucose, and the appropriate culture media in specialized incubators is essential [20], there is no evidence that these factors have any direct instructive function for embryonic pattern (basic body plan) development. They should be seen as nutritional needs in a more general sense [37][38][39]. In earlier years, it had indeed been proposed by some researchers that axis development (the embryonic-abembryonic axis, i.e., the precursor for the dorsoventral axis; the anterior-posterior axis), and the laying down of the basic body plan at gastrulation, might be determined by uterine factors (secreted factors or cellular interactions at implantation).…”
Section: A Recent Discussion About Ethical Guidelines and The Term "E...mentioning
confidence: 99%